Mycotoxigenic Potentials of Fusarium Species in Various Culture Matrices Revealed by Mycotoxin Profiling - Shi, Wen (Toxins (Basel), 2016)
In this study, twenty of the most common Fusarium species were molecularly characterized and inoculated on potato dextrose agar (PDA), rice and maize medium, where thirty three targeted mycotoxins, which might be the secondary metabolites of the identified fungal species, were detected by liquid chromatography–tandem mass spectrometry (LC-MS/MS). Statistical analysis was performed with principal component analysis (PCA) to characterize the mycotoxin profiles for the twenty fungi, suggesting that these fungi species could be discriminated and divided into three groups as follows. Group I, the fusaric acid producers, were defined into two subgroups, namely subgroup I as producers of fusaric acid and fumonisins, comprising of F. proliferatum, F. verticillioides, F. fujikuroi and F. solani, and subgroup II considered to only produce fusaric acid, including F. temperatum, F. subglutinans, F. musae, F. tricinctum, F. oxysporum, F. equiseti, F. sacchari, F. concentricum, F. andiyazi. Group II, as type A trichothecenes producers, included F. langsethiae, F. sporotrichioides, F. polyphialidicum, while Group III were found to mainly produce type B trichothecenes, comprising of F. culmorum, F. poae, F. meridionale and F. graminearum. A comprehensive picture, which presents the mycotoxin-producing patterns by the selected fungal species in various matrices, is obtained for the first time, and thus from an application point of view, provides key information to explore mycotoxigenic potentials of Fusarium species and forecast the Fusarium infestation/mycotoxins contamination.